Total synthesis of jadomycins A, B, and l-digitoxosyl-phenanthroviridin. (6th July 2022) - Akagi, Yusuke; Mori, Yuta; Sato, Yudai; Iwasaki, Erika; Komatsu, Toshiya
Graphical abstract: Abstract: We report the total synthesis of jadomycins A, B, and l -digitoxosyl-phenanthroviridin. 2-Aryl-5-hydroxy-1, 4-naphthoquinones, which were synthesized utilizing a Pd-catalyzed direct arylation of 5-hydroxy-1, 4-naphthoquinone with aryl iodide, were converted into jadomycin A through introduction of l -isoleucine, followed by oxidative cyclization. Mitsunobu reaction of jadomycin A with 3, 4-di- O -acetyl-l -digitoxose, which was prepared from commercially available 3, 4-di- O -acetyl-6-deoxy-l -glucal, followed by deacetylation, gave jadomycin B. Additionally, the first total synthesis of l -digitoxosyl-phenanthroviridin was successful via Mitsunobu reaction of phenanthroviridin aglycon with 3, 4-di- O -acetyl-l -digitoxose.